Causal associations between autoimmune diseases and sarcopenia-related traits: a bi-directional Mendelian randomization study - Chen, Chunlan; He, Ying (Frontiers in Genetics, 2024)
Background: Sarcopenia is common in patients with autoimmune diseases (ADs); however, the causal associations between ADs and sarcopenia remain unclear.Therefore, this study investigated the causal associations by using bi-directional Mendelian randomization analysis.The exposure-related single nucleotide polymorphisms were extracted from genome-wide association studies (GWAS). GWAS statistics for common ADs [Crohn's disease (CD), ulcerative colitis (UC), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), psoriasis (PSO) and multiple sclerosis (MS)] and sarcopenia-related traits [hand grip strength (HGS), appendicular fat-free mass (FFM) and walking pace] were obtained from public datasets. Inverse variance weighting as main method was used to evaluate the causal effect.Results: Genetic predicted CD had causal effects on whole body FFM (β=-0.005, p=0.001), legs FFM (βleft=-0.006, p=1.8E-4; βright=-0.007, p=2.0E-4) and arms FFM (βleft=-0.005, p=0.005; βright=-0.005, p=0.001); while RA had causal effects on eight sarcopenia-related traits including HGS (βleft=-2.06, p=2. 8E-38; βright=-2.311, p=2E-20), whole body FFM (β=-0.842, p=4.7E-10), legs FFM (βleft=-0.666, p=2. and walking pace (β=-1.019, p=6.2E-14). In the reverse direction, HGS (ORleft=10.257, p=3. ORright=16.445, had causal effect on CD; while HGS (ORleft=0.994, p=0.004; ORright=0.993, legs FFM (ORleft=1.003, p=0.005; ORright=1.005, and walking pacing (OR=0.985, p=5.7E-5) were causally associated with RA. No evidence showed causal associations of UC, SLE, PSO or MS with sarcopenia-related traits.Our study demonstrated that the genetic susceptibility to CD and RA was associated with high risk of sarcopenia and some sarcopenia-related traits had causal effects on CD or RA.